Application of Mulching Materials of Rainfall Harvesting System for Improving Soil Water and Corn Growth in Northwest of China - Juan HAN; Zhi-kuan JIA; Qing-fang HAN; Jie ZHANG (Journal of Integrative Agriculture)
The ridge and furrow rainfall harvesting (RFRH) system is used for dryland crop production in northwest of China. To determine the effects of RFRH using different mulching materials on corn growth and water use efficiency (WUE), a field experiment was conducted during 2008–2010 at the Heyang Dryland Experimental Station, China. Four treatments were used in the study. Furrows received uncovered mulching in all RFRH treatments whereas ridges were mulched with plastic film (PF), biodegradable film (BF) or liquid film (LF). A conventional flat field without mulching was used as the control (CK). The results indicated that the average soil water storage at depths of 0–200 cm were 8.2 and 7.3%, respectively higher with PF and BF than with CK. However, LF improved soil water storage during the early growth stage of the crop. Compared with CK, the corn yields with PF and BF were increased by 20.4 and 19.4%, respectively, and WUE with each treatment increased by 23.3 and 21.7%, respectively. There were no significant differences in corn yield or WUE with the PF and BF treatments. The net income was the highest with PF, followed by BF, and the 3-yr average net incomes with these treatments were increased by 2 559 and 2 430 CNY ha−1, respectively, compared with CK. BF and PF had similar effects in enhancing the soil water content, crop yield and net income. Therefore, it can be concluded that biodegradable film may be a sustainable ecological alternative to plastic film for use in the RFRH system in northwest of China.